Thermal resistance and bursting strength analysis of multilayer needle-punched bamboo/polyester nonwoven batt - Abdussalam Al-hakimi Mohd Tahir, Abdussalam Al-hakimi Mohd Tahir; Abdul Rashid, Azrin Hani; Nasir, Siti Hana; MazaAhmad, Mazatusziha; Nor Anuwar, Anis Amirah (Taylor&francis, 2023)
This work aims to evaluate the potential of bamboo/polyester blended needle-punched nonwoven batts as thermal insulators. This research investigated the effects of physical properties on the thermal resistance and the bursting strength subjected to the different number of layers of the batt structure. Bamboo/polyester nonwoven batt was prepared by using a needle-punching technique. The nonwoven batt was made into single, two and three-layers structures termed as 1BP, 2BP and 3BP. Physical properties such as thickness, areal weight, density and porosity were determined to evaluate their relationship with thermal resistance and bursting strength. The properties of bamboo/polyester nonwoven batt were compared with that of polyester nonwoven batt commercially used as insulation layers in comforters. The thermal resistance and bursting strength were found to increase with the increased number of layers and were better than the commercial sample. The ranking shows that density and porosity have the most effect on thermal resistance and bursting strength, followed by areal weight and thickness. High and significant Pearson’s correlation coefficient and P-value indicated that density and porosity are the parameters that mainly influence the thermal resistance of the nonwoven batt. On the other hand, the number of layers was the most influential parameter for bursting strength. Based on the findings, 3BP nonwoven batts exhibited better thermal insulation performance and better strength with the value of 0.2932 m2 K/W and 3.78 kgf, respectively. In comparison, the commercial polyester nonwoven batt recorded a thermal resistance value of 0.2390 m2 K/W and bursting strength of 2.92 kgf.